A Lack of Material Resources Causes Harsher Moral Judgments. (March 2014) - Pitesa, Marko; Thau, Stefan
In the research presented here, we tested the idea that a lack of material resources (e.g., low income) causes people to make harsher moral judgments because a lack of material resources is associated with a lower ability to cope with the effects of others' harmful behavior. Consistent with this idea, results from a large cross-cultural survey (Study 1) showed that both a chronic (due to low income) and a situational (due to inflation) lack of material resources were associated with harsher moral judgments. The effect of inflation was stronger for low-income individuals, whom inflation renders relatively more vulnerable. In a follow-up experiment (Study 2), we manipulated whether participants perceived themselves as lacking material resources by employing different anchors on the scale they used to report their income. The manipulation led participants in the material-resources-lacking condition to make harsher judgments of harmful, but not of nonharmful, transgressions, and this effect was explained by a sense of vulnerability. Alternative explanations were excluded. These results demonstrate a functional and contextually situated nature of moral psychology.